2011
DOI: 10.1159/000330745
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in Inserting 25- and 23-Gauge Trocar Cannula during Vitrectomy

Abstract: Purpose: To determine the incidence of difficulty in inserting a 25- and 23-gauge trocar cannula (DITC) during 25- or 23-gauge micro-incision vitrectomy surgery (MIVS). Methods: Retrospective, consecutive, interventional case series performed by a single surgeon at a single centre. We defined a DITC as the condition where at least 1 trocar cannula could not be inserted into the vitreous at the beginning of MIVS. The incidence of DITC was calculated from 1,525 eyes, and the pre-operative demographics of the DIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…15 Some patients (%1.0%) should have microincision vitrectomy surgery with caution. 16 However, the indication for 25-gauge microincision vitrectomy has expanded to various diseases, including PDR, RRD, giant retinal tear detachment, intraocular foreign body, and IOL dislocation, 17-25 because of the Table 2). Lower: A 60-year-old man with RRD (eye 20, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…15 Some patients (%1.0%) should have microincision vitrectomy surgery with caution. 16 However, the indication for 25-gauge microincision vitrectomy has expanded to various diseases, including PDR, RRD, giant retinal tear detachment, intraocular foreign body, and IOL dislocation, 17-25 because of the Table 2). Lower: A 60-year-old man with RRD (eye 20, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 25GMIVS allows earlier postoperative visual improvement than 20GPPV and does not induce significant changes in the corneal topography or optical quality of the cornea [1620]. Although 25GMIVS does have limitations [21–23], we believe that because it is sutureless, it is the best choice to treat retinal disease in eyes with preexisting TLE and can best preserve the filtering bleb. However, to the best of our knowledge, using the PubMed search system, there are no reports discussing or evaluating the use of 25GMIVS to treat retinal diseases in glaucomatous eyes after TLE, except one case report of familial amyloid polyneuropathy (FAP) [24].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study reviewing difficulties in trocar insertion showed that it was not possible to safely insert at least one 23- or 25-gauge trocar cannula into a quarter of eyes with a preoperative intraocular pressure of less than 8 mmHg. [ 3 ] Instead, vitrector-assisted sclerotomy had to be performed. Other articles discuss complications such as inadvertent posterior capsule rupture due to the amount of deformity caused by trocar insertion into a hypotonous eye.…”
mentioning
confidence: 99%